Diseño de un Manual de Control Interno Administrativo, Contable y Tributario para el Gobierno Autónomo Descentralizado Parroquial Rural de Cumbaratza del Cantón Zamora - Pullaguari Paccha, Cindi Mariuxi (2023)
The present work of curricular integration called Design of an internal administrative, accounting and tax control, manual for the rural pans decentralized autonomous government of Cumbaratza of the Zamora Canton, it was executed in order to develop a support and guidance instrument in the execution of procedures promoting effiency, effectiveness and optimization that allows the institution to improve and guide administrative, accounting and tax activities. For the preparation of this work, an interview was carried out with the president and account to identify internal administrative, accounting and tax deficiencies, thus gathering information on the level of knowledge of their activities and operations. In order to comply with the objectives, the administrative, accounting and tax procedures of the Autonomous Rural Parochial Decentralized Government were identified, in administrative manual was design for the personnel develop their activities in an orderly manner, policies and procedures were carried out. Flowcharts focused on the administrative process, recruitment and selection processes for personnel, training and procedures, attendance control, vacations and personnel evaluation. Regarding the accounting part, policies and procedures were designed with their respective standard entries, formats and flowcharts, which focus on establishing internal controls for the accounts that contribute the most and affect the accounting process, with the purpose of carrying out a correct development of the activities, tax policies and procedures were developed in order to verify the processes in the presentation of statements and annexes. Finally, flowcharts were developed for each procedure, according to the activities carried out by the institution, in order to follow the steps in sequence and thus improve the administration of the GAD. At the end of the work of Curricular Integration, it was determined that an internal administrative accounting and tax control manual for the Rural Decentralized Autonomous Government of Cumbaratza , constitutes a tool that allows the authorities and officials of the entity, and instrument of great importance for management institution to facilitate the fulfillment of the activities to be carried out, improve the effiency of tasks, and contribute to obtaining detailed and orderly information.